(untitled) (The Review of Diabetic Studies, 2025)
Background: Dengue fever is a major public health challenge in the western coastal areas of Saudi Arabia, such as the Medina. Religious gatherings in this area increase the risk of transmission. The city’s unique demographic composition and environmental factors create distinctive challenges for dengue surveillance and control. Objective: To analyze the epidemiological characteristics and laboratory findings of dengue fever cases in Medina from January to November 2023, examining demographic patterns, geographical clustering, seasonal variations, and key laboratory parameters. Methodology: A cross-sectional study was conducted to analyze 202 dengue cases. Laboratory confirmation utilized Reverse Transcription-Polymerase Chain Reaction (RT-PCR), Non-Structural Protein 1 (NS1) antigen, and Immunoglobulin M (IgM) antibody testing. Data analysis included demographic characteristics, geographical distribution, seasonal patterns, and laboratory parameters including White Blood Cell (WBC), Platelet (PLT), Hematocrit (HCT), and Liver Function Tests (LFTs) comprising Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT). Statistical analysis was performed using R version 4.0.3. Results: Demographic analysis revealed male predominance. Temporal analysis revealed significant summer predominance. Diagnostic evaluation demonstrated Reverse Transcription-Polymerase Chain Reaction (RT-PCR) yielding highest sensitivity, followed by Non-Structural Protein 1 (NS1) and Immunoglobulin M (IgM). Age-stratified analysis revealed optimal diagnostic response across all testing modalities in patients aged < 20 years, while those aged 20 − 35 years exhibited superior RT-PCR and NS1 performance. Diagnostic efficacy in advanced age demonstrated NS1 and IgM superiority among patients aged > 65 years. Hematological evaluation revealed characteristic White Blood Cell countreduction, Platelet count reduction, and preserved Hematocrit levels. Hepatic enzyme analysis demonstrated elevated median values for Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT). Conclusion: The study demonstrated distinctive epidemiological and laboratory patterns, characterized by demographic heterogeneity, temporal-spatial clustering, differential diagnostic sensitivities, andcharacteristic hematological-hepatic profiles. These comprehensive findings advocate for integrated surveillance strategies during peak transmission periods